Exposure to the insecticide sulfoxaflor affects behaviour and biomarkers responses of Carcinus maenas (Crustacea: Decapoda) - Damasceno, Jadilson M. (2022)
Sulfoxaflor is an insecticide belonging to the recent sulfoximine class, acting as a nicotinic acetylcholine receptor (nAChRs) agonist. There are few studies regarding sulfoxaflor’s toxicity to non-target organisms. The present study aimed to investigate the acute and sub-lethal effects of sulfoxaflor on Carcinus maenas by addressing survival, behaviour (feed intake and motricity), and neuromuscular, detoxification and oxidative stress, and energy metabolism biomarkers. Adult male green crabs were exposed to sulfoxaflor for 96 h and an LC50 of 2.88 mg L1 was estimated. All biomarker endpoints were sampled after three (T3) and seven (T7) days of exposure and behavioural endpoints were addressed at T3 and day six (T6). Sulfoxaflor affected the feed intake and motricity of C. maenas at T6. From the integrated analysis of endpoints, with the increase in concentrations of sulfoxaflor, after seven days, one can notice a lower detoxification capacity (lower GST), higher LPO levels and effects on behaviour (higher motricity effects and lower feed intake). This integrated approach proved to be valuable in understanding the negative impacts of sulfoxaflor on green crabs, while contributing to the knowledge of this pesticide toxicity to non-target coastal invertebrates.